"Something is just not right with my hearing": early experiences of adults living with hearing loss. (2nd September 2022) - Pike, April; Moodie, Sheila; Parsons, Karen; Griffin, Anne; Smith-Young, Joanne; Young, Terry-Lynn; Mills, Leon; Barrett, Myrtle; Rowe, Leanna; Parsons, Marie; Kielley, Henry; Fleming, Michael
Abstract: Objective: To understand the psychosocial process of how adults experience hearing loss; specifically, their readiness to accept that they may have hearing loss, and the challenges and coping strategies associated with it. Design: A grounded theory methodology guided the research. A patient-orientated research approach informed the study. Thirty-nine individual interviews and six focus groups were completed. Study sample: Participants included 68 individuals aged 50 years and older with self-reported hearing loss living in Newfoundland and Labrador. Results: The theoretical construct, 'Realising that something is just not quite right with my hearing' captured individuals' experiences as they gradually awakened to the fact that they had hearing loss. Three categories describe the process: (1) Rationalising suspicions, (2) Managing the invisible and (3) Reaching a turning point. Conclusions: Many individuals do not recognise hearing loss in its early stages, although they may be already experiencing its negative effects. It is important to identify motivators to engage individuals as early as possible in their hearing health. Taking a proactive approach to hearing health can help mitigate the potential negative outcomes of hearing loss.